2002
DOI: 10.1136/gut.51.6.832
|View full text |Cite
|
Sign up to set email alerts
|

Trends in indigenous foodborne disease and deaths, England and Wales: 1992 to 2000

Abstract: Background: Commitment to food safety is evidenced by high profile governmental initiatives around the globe. To measure progress towards targets, policy makers need to know the baseline from which they started. Aim: To describe the burden (mortality, morbidity, new presentations to general practice, hospital admissions, and hospital occupancy) and trends of indigenous foodborne disease (IFD) in England and Wales between 1992 and 2000. Methods: Routinely available surveillance data, special survey data, and ho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
304
7
2

Year Published

2002
2002
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 414 publications
(319 citation statements)
references
References 16 publications
6
304
7
2
Order By: Relevance
“…Reconstructing the surveillance pyramid provides important information for interpretation of reported data, and provision of incidence estimates that can be meaningfully compared. Such studies are attractive as they are relatively easy to perform in comparison to population-based surveys such as the IID studies in the UK [4,5] and the Sensor study in The Netherlands [6]. Our results confirm that the degree of underreporting varies widely by pathogen and by country.…”
Section: Overview Of Resultssupporting
confidence: 76%
See 1 more Smart Citation
“…Reconstructing the surveillance pyramid provides important information for interpretation of reported data, and provision of incidence estimates that can be meaningfully compared. Such studies are attractive as they are relatively easy to perform in comparison to population-based surveys such as the IID studies in the UK [4,5] and the Sensor study in The Netherlands [6]. Our results confirm that the degree of underreporting varies widely by pathogen and by country.…”
Section: Overview Of Resultssupporting
confidence: 76%
“…In England and Wales, the IID1 study estimated that in 1993-1996 there were 3 . 2 cases of salmonellosis in the population for every case reported to national surveillance [4]. The recently published IID2 study indicated that in [2008][2009], this multiplier had increased to 4 .…”
Section: Introductionmentioning
confidence: 99%
“…For example, Salmonella infection causes more deaths annually than any other foodborne pathogen in England and Wales [1]. Within Europe, Salmonella sp.…”
Section: Introductionmentioning
confidence: 99%
“…like outbreak-based attribution efforts by cSPI (2009), cDc (Painter et al 2009) and public health agencies in the United kingdom (Adak et al 2002), our approach involves three steps. First, outbreak data is aggregated over some a defined time period.…”
Section: Outbreak Attributionmentioning
confidence: 99%
“…The most comprehensive primary data source available in the U.S. that can be used for food attribution of foodborne illness is cDc's outbreak surveillance data. numerous categorization schemes have been used to analyze outbreak data for food attribution patterns, including those developed by the Uk Health Protection Agency centre for Infections (HPA) (Adak et al 2002), by cDc (Painter et al 2009), and by the center for Science in the Public Interest (cSPI) (2009).…”
Section: Food Categorizationmentioning
confidence: 99%